0
$\begingroup$

For a linear, inhomogenous ordinary differential equation:

$ \dfrac{dy}{dx} + 2y = 4x^2 +6x -1$

$(a)$ Find one solution to equation above that is quadratic. ie. of the form $P(x) = Ax^2 +Bx + C$

I used the integrating factor and find out that $y = 2x^2 +x -1$

$(b)$ solve the homogeneous linear equation $\dfrac{dy}{dx} + 2y = 0$

And my solution is $y = e^{-2x+C}$ or $y=0$

$(c)$ Solve $ \dfrac{dy}{dx} + 2y = 4x^2 +6x -1$ using $(a)$ and $(b)$. Hint: given a solution $y$ to $ \dfrac{dy}{dx} + 2y = 4x^2 +6x -1$, show that $y-P$ is a solution to a nice equation.

I don't really understand part $(c)$. Can anyone give me some hints?

$\endgroup$
  • $\begingroup$ The ODE is linear. If $y_k$, $k=1,2$, is such that $y_k'+2y_k=f_k$, then $y=y_1+y_2$ is such that $y'+2y=f_1+f_2$. $\endgroup$ – Pocho la pantera Sep 18 '13 at 21:36
0
$\begingroup$

If $L(y)$ is a linear differential operator, for example $L(y) = y'+2y$ as in your case, then every solution to $L(y) = f$ can be written as $$y = y_h + y_p$$ where $y_h$ is a solution to the homogeneous equation $L(y) = 0$ and $y_p$ is a particular solution to $L(y) = f$.

Proof. Let $y$ be an arbitrary solution to $L(y) = f$. Then $L(y-y_p) = L(y) - L(y_p) = f - f = 0$. Hence $y-y_p$ solves the homogeneous equation.

Conversely, if $y_h$ and $y_p$ are as above, then $y = y_h + y_p$ solves $L(y) = f$.

Proof. $L(y_h + y_p) = L(y_h) + L(y_p) = 0 + f = f$.

Notice the importance of $L$ being linear.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.